The role of creative leadership in achieving institutional excellence - A field study at King Abdulaziz University in Jeddah (1444 AH - 2023 AD) - Alshekhi, Ahmed Hassan; Mujallid, Osama AbdulRahman (Journal of Economic, Administrative and Legal Sciences, 2023)
This study aimed to identify the role of creative leadership in its dimensions (sensitivity to problems, fluency, flexibility, originality) in achieving institutional excellence. To achieve this goal, the researcher used the analytical descriptive approach, by distributing a questionnaire to a simple random sample of (80) from the study population, The results of the study showed that there is a role for creative leadership in each of its dimensions in achieving institutional excellence, In light of the previous results, the study recommended: Activating the role of creative leadership in achieving institutional excellence, and the need to look at institutional excellence and pay attention to it according to creative thought.